Reproduction and parenthood among lesbian couples in China: Legal and ethical perspectives - Fu, Huixian (Bioethics, 2024)
In China, neither reproduction and parenthood by lesbian couples nor their marital status are regulated or protected by law. In 2020, the first legal dispute in China involving a lesbian couple over custody of their joint baby was heard in court. This study examines the legal and ethical issues that lesbian couples confront when they decide to give birth to a child of their own. These challenges begin with regulatory restrictions on their lawful access to assisted reproductive technology and extend to gaps in the legal establishment of parenthood. We found that the lack of access to legitimate reproductive assistance for lesbian couples in China has caused them to make efforts to circumvent laws and regulations to have a child. However, the legislative gaps later led to ethical dilemmas when resolving disputes over parenthood. This study discusses different accounts of establishing and determining natural parenthood in China and concludes by pointing out the urgent need for change in legislative and sociocultural attitudes toward both assisted reproductive technology and same-sex relationships, mapping the way forward for lesbian couples to obtain better protection of procreation and parenthood before their marriage is culturally accepted and finally legalized.